1991
DOI: 10.1073/pnas.88.12.5134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical menopause and estrogen replacement on cytokine release from human blood mononuclear cells.

Abstract: To determine whether mononuclear cell secretory products contribute to the changes in bone turnover that characterize the development of postmenopausal osteoporosis, we evaluated the effects of oophorectomy and subsequent estrogen replacement on the spontaneous secretion of interleukin 1 (IL-1) and tumor necrosis factor a (TNF-a) and on the phytohemagglutinin A-induced secretion of granulocyte-macrophage colony-stimulating factor (GM-CSF) from peripheral blood mononuclear cells. In 15 healthy premenopausal wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
276
2
11

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(296 citation statements)
references
References 56 publications
7
276
2
11
Order By: Relevance
“…Estrogen withdrawal after ovariectomy or natural menopause is associated with increased production of TNF-␣ and IL-1 (37,38), both of which increase LTB 4 production in neutrophils (44) and macrophages (45). LPS was also reported to increase LTB 4 production in both cell types (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen withdrawal after ovariectomy or natural menopause is associated with increased production of TNF-␣ and IL-1 (37,38), both of which increase LTB 4 production in neutrophils (44) and macrophages (45). LPS was also reported to increase LTB 4 production in both cell types (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Several ex vivo studies have shown that estrogen deficiency causes spontaneous increase in pro-inflammatory cytokine levels, such as interleukin 1 (IL-1), interleukin 6 (IL-6) and tumour necrosis factor alpha (TNF-α) in circulating monocytes (Pacifici, et al 1989, Pacifici, et al 1991, bone marrow macrophages (Jilka, et al 1992, Bismar, et al 1995 and osteoblasts (Passeri, et al 1993). In contrast, in vivo studies in tissue samples or circulation have not been able to clearly demonstrate the effects of estrogen deficiency on pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that increased IL-1 production by human peripheral blood mononuclear cells (PBMCs) is responsible for development of osteoporosis [12,13]. It has been also reported that increased osteoclastogenesis and bone resorption in ovariectomized mice was inhibited by IL-1 receptor antagonists, suggesting that endogenous IL-1 plays an important role in osteoclastic bone resorption in vivo [14].…”
Section: Osteoclastsmentioning
confidence: 99%
“…Monocyte infiltration is thought to be triggered by various chemoattractants and cytokines including IL-1 [18,19]. Increased secretion levels of IL-1 activity by PBMCs have been reported in postmenopausal women [13]. Concentration levels of IL-1 secreted by PBMCs from patients with periodontal disease [22] and those in tissues from sites of periodontal disease [1] are 0.45-13.00 ng/ml/ 106 cells/24 h and approximately 11 ng/ml, respectively.…”
Section: Il-1~3 Stimulates the Formation Of Trap Positive Mncs From Pmentioning
confidence: 99%